Pengelolaan Lingkungan Belajar Mengenai Alat Permainan Edukatif (APE) untuk Meningkatkan Minat Belajar di TK Khalifah - Risbon Sianturi; Windy Fattikasari; Nur Anis (AIJER: Algazali International Journal Of Educational Research, 2023)
Abstrak: Management of the Learning Environment Regarding Educational Game Tools (APE) to Increase Learning Interest in Khalifa Kindergarten.  This study aims to increase interest in learning in early childhood through the use of educational support tools using descriptive qualitative research methods. The data collection technique carried out by researchers is by conducting interviews with the Principal of Khalifah Kindergarten by filling out questionnaires. The purpose of using educational support tools (APE) in Khalifah Kindergarten is to increase interest in learning in students. APE can help increase students' motivation and interest in learning through more engaging and interactive ways. Some of the benefits of using APE include; Enriching the learning experience, APE can provide a more varied and interesting learning experience, so that students can be more involved in the teaching-learning process; Increasing creativity and imagination, namely APE can trigger the creativity and imagination of students by presenting more visual and interactive material; Improving memory i.e. APE can help learners to more easily remember the information provided, due to the use of more interesting visuals and audio; Increase participation, namely APE can increase student participation in the teaching-learning process, because the material presented is more interesting and interactive. In the context of Khalifa Kindergarten, the use of APE can help increase students' interest in learning, especially for material that is difficult to understand in conventional ways. With the use of APE, students can learn more enjoyably and experience a more varied learning experience. As a result, it is expected that students' interest in learning can increase and create a more active and dynamic learning atmosphere.